The Effectiveness of a Nurse-led Team-Based Hypertension Management among People with Uncontrolled Hypertension in a Community Hospital, Thailand - Nongnut Oba; Navarat Chutipanyaporn (Universitas Airlangga, 2021)
Introduction: Uncontrolled blood pressure of people with hypertension remains a major public health issue. The purpose of this research was to evaluate the effectiveness of a Nurse-led Team-based Hypertension Management Program (NTHMP) among people with uncontrolled hypertension.Methods: This quasi-experimental one-group pre-posttest design research was done to evaluate the effectiveness of a NTHMP in a community hospital in Thailand. The sample was thirty people with uncontrolled hypertension who received outpatient care in a community hospital in Thailand. They participated in three months NTHMP which included 1) team-approached health education, 2) medication administration support, 3) motivation interviewing on behavioral adjustment and 4) home blood pressure monitoring for three months. Outcomes of the program; systolic blood pressure, diastolic blood pressure, hospital admissions with signs of hypertensive urgency were analyzed by using frequency, percentage, mean, standard deviation, and repeated measured ANOVA.Results: The results indicated that people with uncontrolled HT had lower systolic blood pressures and diastolic blood pressure compared with baseline levels (p<0.001), and no hospital admissions.Conclusion: This program provided evidence for nurses to manage blood pressure control in people with hypertension within a collaboration with multidisciplinary team members in the community hospital.